Multiple slope failures associated with neotectonic activity in the Southern Central Andes (37° -37°30's), Patagonia, Argentina - Penna, Ivanna Marina (2011)
Quaternary tectonic activity in the transition area between the Central and Patagonian Andes is closely associated with an anomalous cluster of rockslides: 19 rockslides with volumes up to 4 × 109 m3 developed in plateau basalts. We divided them into two groups: (A) rockslides related to neotectonic activity and (B) rockslides not related to neotectonic activity. Thirteen rockslides, with a total volume of ~10 km3, which lie on either folds or faults, have been displaced parallel to the structures and perpendicular to the valleyaxis, and they exhibit headscarps several kilometersaway from the valley axis. Most of them are larger than 109 m3, and are generally of rock avalanche type with a high degree of crushing of rocks, although local relief in some cases does not exceed 200 m. Nine rockslides with a total volume of 8.9 km3 are related to folds, while four with a total volume of 1.3 km3 are related to faults. The six rockslides not related to neotectonic activity have a totalvolume of 0.25 km3 (of which the largest one accounts for 0.17 km3), and are rotational slides and block topples with a low degree of rock fragmentation, although local relief is up to 400 m. The 3He and 21Ne surface exposure ages for six of these slides, as well as relative age assessment based on stratigraphic relation with glacial deposits and the drainage development on the rockslide deposit, suggest that the rockslide ages spread rather randomly betweenpre-glacial and mid Holocene, discarding climatic conditions as a common triggering factor. The absence of structures that can represent ideal sliding planes shows that rock fracturing due to neotectonic activity is a major conditioning factor for failures and that the magnitude of landslides is strongly controlled by the type of deformation.